Lectures on geophysical fluid dynamics - Salmon, Rick (Oxford University Press, 1998)
Lectures on Geophysical Fluid Dynamics offers an introduction to several topics in theoretical geophysical fluid dynamics, including the theory of large-scale ocean circulation, geostrophic turbulence, and Hamiltonian fluid dynamics. The book is based on an introductory course in dynamical oceanography offered to first-year graduate students at Scripps Institution of Oceanography. Each chapter is a self-contained introduction ti its particular subject, and makes few specific references to other chapters. Chapters 1 examines the relationship between the molecular and continuum models of the fluid, and between the Eulerian and Lagrangian descriptions of the latter. Ch.2 is a broad introduction to the fluid dynamics of rotating, stratified flows. Ch.3 adddresses large-scale ocean circulation. Chs.4,5 and 6 discuss the theory of turbulence, including elementary ideas based on vorticity laws (Ch.4), statistical turbulence theory (Ch.5), and the applications of these ideas to quasigeostrophic flows in the Earth's oceans and atmosphere (Ch.6). Ch.7 surveys Hamiltonoian fluid dynamics, including the interaction between waves and currents, and "balanced" approximations to nearly geostrophic; Overall, the emphasis is on physical ideas rather than mathematical techniques. Readers are assumed to have had an elementary introduction to fluid mechanics, to know advanced calculus through partial differential equations, and to be familiar with the elementary ideas about linear waves, including the concept of group velocity.